The place of “Southwestern” Khanty among the Khanty dialects: the testimony of phonology and morphology - Fejes, László (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2023)
Southwestern Khanty is a dialect documented only in the 2008 PhD dissertation by Olga Vaysman. A previous study based on lexical data established that Southwestern Khanty is very close to Obdorsk Khanty. The current study explores the dialect’s phonological and morphological features. Although some of these features are typical only of Obdorsk Khanty among the formerly known dialects, some features of Southwestern Khanty are unique among the Khanty dialects. These peculiarities of Southwestern Khanty are numerous and unsystematic, which makes it unlikely that the dialect developed from Obdorsk Khanty or a dialect near Obdorsk Khanty. Taking into account the obscurity of the metadata, it is questionable whether Vaysman’s data on Southwestern Khanty really reflect the linguistic facts of an existing Khanty dialect. Kokkuvõte. László Fejes: “Edelahandi” paiknemine handi murrete hulgas: tõendid fonoloogiast ja morfoloogiast. Edelahandi murre on dokumenteeritud ainult Olga Vaysmani 2008. aasta doktoritöös. Eelmine, leksikaalsetel andmetel põhinev uuring näitas, et edelahandi on lähedane Obdorski handile. Käesolev uuring analüüsib edelahandi fonoloogilisi ja morfoloogilisi tunnuseid. Kuigi mõned neist tunnustest on varem tuntud murrete hulgas tüüpiliseid ainult Obdorski handile, on mõned omadused handi murrete seas ainulaadsed. Need edelahantide eripärad on arvukad ja ebasüstemaatilised, mistõttu on ebatõenäoline, et edelahandi arenes välja Obdorski handi murdest või selle lähedasest murdest. Võttes arvesse metaandmete hämarust, on küsitav, kas Vaysmani andmed edelahandi kohta kajastavad tõesti olemasoleva handi murde keelelisi fakte.